2004
DOI: 10.2174/1566523044578077
|View full text |Cite
|
Sign up to set email alerts
|

Promoters and Control Elements: Designing Expression Cassettes for Gene Therapy

Abstract: It has become apparent that the clinical success anticipated in the field of gene therapy has been limited by progress in several of the fundamental areas of genetics, molecular and cellular biology relevant to its application. Whilst a great deal of effort has been made in the evaluation of transgenes, it is only more recently with the advance of vector systems that attention has begun to be focused upon the means and control of transgene expression. Until recently, the majority of constructs have employed ub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
121
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 262 publications
(248 reference statements)
2
121
0
1
Order By: Relevance
“…While CMV is a strong viral promoter, several mechanisms have been proposed for transient expression, such as deletion of transduced cells or promoter downregulation. [30][31][32] Even if results of this study suggest that the vector construct containing the CMV promoter was more successful than MND, we cannot conclude that CMV is a more efficient promoter than MND because the quantity of virus injected differed. These results do, however, suggest that the level of transduction is dose-dependent, Figure 6 Whole-tissue fluorescence.…”
Section: Discussionmentioning
confidence: 70%
“…While CMV is a strong viral promoter, several mechanisms have been proposed for transient expression, such as deletion of transduced cells or promoter downregulation. [30][31][32] Even if results of this study suggest that the vector construct containing the CMV promoter was more successful than MND, we cannot conclude that CMV is a more efficient promoter than MND because the quantity of virus injected differed. These results do, however, suggest that the level of transduction is dose-dependent, Figure 6 Whole-tissue fluorescence.…”
Section: Discussionmentioning
confidence: 70%
“…Consequently, insulators application in multigene constructs is ergonomically beneficial. Insulator sequences guarantee genes autonomy because they determine the compartments in the molecular environment of DNA strands, whereby separating the influence of chromatin state and regulators related to adjacent genes (Papadakis et al 2004;Yang et al 2011).…”
Section: Insulator Sequencesmentioning
confidence: 99%
“…They neutralize the position effect, and the influence of adjacent sequences on gene expression (Papadakis et al 2004;Allen 2008), thus protecting genes against undesirable silencing by heterochromatin. Euchromatin domains are separated from heterochromatin by MAR sequences (matrix associated region), known also as SAR (scaffold attachment region), characterized by a high content of AT base pairs.…”
Section: ′Utr Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…The transient expression obtained with first-generation Ad vectors is well known, and lately it was found that the major mechanism behind the decreased expression observed was transcriptional silencing due to methylation of the CMV promoter. 21 Silencing is most likely a consequence of the origin of the sequences in the promoter, and even though the over time fate of the 2hE-hTyrP promoter has not been investigated, we hypothesize that silencing of this construct is less likely to occur, as it contains only human sequences (for review see Papadakis et al 22 ).…”
Section: Discussionmentioning
confidence: 99%